2010
DOI: 10.2214/ajr.09.3301
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Balloon Inflation Elastography for Prostate Cancer Detection and Initial Evaluation of Clinicopathologic Analysis

Abstract: The RBIE method improved the quality of elastographic moving images compared with the manual compression method. High-grade tumors and tumors of impalpable regions of the prostate were more frequently detected using RBIE. We conclude that RBIE is a promising method with which to detect prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 23 publications
0
43
0
Order By: Relevance
“…Apart from liver imaging, it has many other clinical applications that have been reported in the literature, such as breast, thyroid, prostate and pancreas [33,34,35,36]. RTE image is constructed using tissue strains which are calculated from 2 consecutive frames.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from liver imaging, it has many other clinical applications that have been reported in the literature, such as breast, thyroid, prostate and pancreas [33,34,35,36]. RTE image is constructed using tissue strains which are calculated from 2 consecutive frames.…”
Section: Introductionmentioning
confidence: 99%
“…To address this challenge, Tsutsumi et al inflated a water balloon surrounding the transducer to compress the tissue, which reduced the operator dependence of the image quality. Using this method, the authors detected 71 % of histology confirmed PCa lesions [32]. [5] Overall, the multitude of studies performed using strain imaging has demonstrated great promise for guidance of targeted biopsies.…”
Section: Elastographic Imaging Methods In Prostate Strain Imagingmentioning
confidence: 99%
“…A skilled technician is needed to obtain adequately uniform compression, which can be challenging. Some recent studies have used inflatable balloons that surround the endorectal transducer and can be filled or emptied by the operator, thereby generating a more uniform stress on the prostate [27,31,32].…”
Section: Elastographic Imaging Methods In Prostate Strain Imagingmentioning
confidence: 99%
“…An inflated balloon filled with water may be placed between the probe and the rectal wall to achieve more uniform compression. The difference in tissue displacement from one frame to another is used to generate an elastogram, which is a color map of local tissue strain (34). In a metaanalysis by Aboumarzouk et al (35), the sensitivity and specificity of SE were in the range of 71%-82% and 60%-95%, respectively, with radical prostatectomy specimens as the reference standard.…”
Section: Ultrasound Elastographymentioning
confidence: 99%